Generation Priced Out Who Gets to Live in the New Urban America, with a New Preface. - Shaw, Randy (University of California Press, 2020)
Generation Priced Out is a call to action on one of the most talked-about issues of our time: how skyrocketing rents and home values are pricing the working and middle classes out of urban America. Randy Shaw tells the powerful stories of tenants, politicians, homeowner groups, developers, and activists in over a dozen cities impacted by the national housing crisis. From San Francisco to New York, Seattle to Denver, and Los Angeles to Austin, Generation Priced Out challenges progressive cities to reverse rising economic and racial inequality. Shaw exposes how boomer homeowners restrict mille.